The effectiveness of electrocoagulation process in latex wastewater treatment in comparison to conventional physical treatment / Praimon N Janagarajan - Praimon, N Janagarajan (2021)
distance (cm) and time (seconds). Using the optimal values obtained, other parameters of the wastewater sample were analyzed to determine if Department of Environment (DOE) Standard B criteria could be achieved or not. There was significant reduction in the pollutant parameters in comparison to the conventional physical treatment which has been installed in the selected company. This shows that electrocoagulation is an efficient treatment process in the treatment of wastewater from latex industry. But electrocoagulation alone could not achieve DOE Standard B effluent discharge standard. The aid of biological treatment is required to further reduce the pollutant concentration.